Novel Approach for Designing Dual-Band 5G Antenna Integrated Reflector - Faridani, Mohammad (Université d'Ottawa / University of Ottawa, 2023)
As the world continues to adopt the next generation of mobile technology, dual-band 5G wireless communications are becoming increasingly significant. 5G technology operates on two different frequency bands, the sub-6 GHz Frequency Range (FR1) and the millimeter wave (MMW) Frequency Range (FR2). The special features in each band enable 5G dual-band communication to provide better coverage and capacity than previous generations of wireless networks. This is especially essential for applications that need high-bandwidth and low-latency connections, such as virtual and augmented reality, autonomous vehicles, and industrial automation. Furthermore, dual-band 5G can help alleviate network congestion in urban areas by redirecting traffic to the MMW band, which has considerably greater capacity. As a result, dual-band 5G is expected to play a critical role in facilitating the next wave of technological innovation and revolutionizing the way we live and work. A dual-band antenna with a large frequency ratio (FR) is required due to the significant difference between each frequency band in 5G. Research on dual-band antennas is facing challenges such as low FR and a lack of a specific design methodology. Despite attempts to develop dual-band antennas with large FRs, there are still issues with low performance and limited bandwidth. This study introduces a novel approach for designing a dual-band antenna with a large FR. The proposed solution draws inspiration from a hybrid design of a dual-band antenna to achieve a large FR, and from the parabolic reflector antenna design to significantly enhance gain in the upper band. The lower band antenna in this design serves as both a radiator for the lower band and a reflector to align the beam in the upper band. This approach can be used to design dual-band antennas for various frequencies. In this thesis, we present a comprehensive model and framework for designing an antenna integrated reflector that offers a large FR. The proposed model is capable of producing an antenna that meets the requirements of the targeted application, namely 5G. This antenna exhibits wideband characteristics and high gain. Two different antenna integrated reflectors, named AIR-I and AIR-II, were designed based on the proposed model. AIR-I has a FR of 10.1. As for AIR-II, due to the presence of dual-band upper antennas, it has a lower band at 1.35 GHz and two upper bands at 13 GHz and 24 GHz thus, a FR of 9.5 and 18, respectively. The above design followed a specific purpose. It uses a 24 GHz/1.35 GHz frequency ratio of 18 to showcase the antenna performance in the context of dual-band 5G. However, the measurement facilities being limited to 20 GHz, a frequency ratio of 9.5 at 13 GHz/1.35 GHz was measured for the AIR-II, as proof of concept. Then, two prototypes were fabricated from AIR-II namely, Prototype-I and Prototype-II. While it would have been possible to demonstrate a proof of concept from a single prototype, it has been decided to produce and test two samples to enable a more exhaustive examination of the subject and obtain additional data that would lend greater support to the model outlined in this thesis. Prototype-I had the same structure as AIR-II and had an operational bandwidth of 0.69 GHz-1.74 GHz / 6 GHz-18 GHz and a FR of 9.9. On the other hand, Prototype-II had an operational bandwidth of 0.69 GHz-1.74 GHz / 13 GHz-18 GHz and a FR of 12.8. These prototypes exhibited maximum bandwidths of 100% and 86%, respectively. Furthermore, at the upper band, Prototype-I achieved a peak gain improvement of 12.6 dB, while Prototype-II achieved an improvement of 8.7 dB. These results demonstrated the significant advantages of our proposed methodology in dual-band antenna design.
Keywords: antenna; 5G; dual-band; reflector